El derecho constitucional a la reparación integral de las víctimas en la práctica de la justicia indígena. - Quilca, Iván J. (2022)
The integral reparation is the legal institution that is contemplated within the Ecuadorian law, its purpose is to protect the victim’s rights and in function of the legal security to establish the mechanisms of restitution of the caused damage. The present document had the objective to analyze the integral reparation of the victims of the practice of the indigenous justice in the current Ecuadorian law. For this instance, from the document research and a legal social investigation, it was employed a contentive survey of 14 questions directed to the indigenous communities and particularly to the Miguel Egas community. The results permitted to affirm that ancestral law is applied, restorative and customary, and the result was concluded that there is no legal pertinent mandate to apply the integral reparation as a measure that guaranties the compensation for the vulnerable rights of the victims as it happens in the ordinary justice. Consequently, it is essential that the ordinary justice similar to the indigenous justice, make use of this figure of voluntary form.